Green growth indicators 2014. - (:unkn) unknown (My University, 2014)
Die "Green Growth Indicators 2014" sind nach vier Hauptzielen gegliedert: Schaffung einer CO2-armen, ressourceneffizienten Wirtschaft, Erhalt des Naturkapitals, Verbesserung der Lebensqualität der Bevölkerung sowie Umsetzung geeigneter Politikmaßnahmen und Nutzung der durch umweltverträgliches Wachstum ("Green Growth") gebotenen wirtschaftlichen Chancen.
Policies that promote green growth need to be founded on a good understanding of the different factors that affect green growth, and appropriate information is needed to monitor progress and measure results. Monitoring progress towards green growth requires indicators based on internationally comparable data. These need to be embedded in a conceptual framework and selected according to well specified criteria. Ultimately, they need to be capable of sending clear messages which speak to policy makers and the public at large. As part of its Green Growth Strategy, the OECD has developed a conceptual framework and indicators that help governments monitor progress towards green growth. "Green Growth Indicators 2014" updates the 2011 Towards Green Growth: Monitoring progress. It presents the OECD framework for monitoring progress towards green growth and a selection of updated indicators that illustrate the progress that OECD countries have made since the 1990s. Moreover, countries like the Czech Republic, Denmark, Germany, Korea, the Netherlands and the Slovak Republic have already applied and adjusted the OECD green growth measurement framework and indicators to their specific national contexts to assess their state of green growth. With the support of OECD, the Latin America Development Bank, the Latin American and the Caribbean Economic System and the United Nations Industrial Development Organization, work is underway in Mexico, Colombia, Costa Rica, Ecuador, Guatemala, Paraguay and Peru to apply the OECD indicators as a way to identify key areas of national concern and the scope for improving the design, choice and performance of policy instruments.
Keywords: Umweltschutz; Umweltpolitik; Wirtschaftswachstum; Umweltziel; Nachhaltige Entwicklung